KEPEMIMPINAN DI SEKOLAH DALAM MENGHADAPI PARADIGMA BARU PENDIDIKAN DI INDONESIA - lis Prasetyo (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Democratization and decentralize of education represent one of central agenda in reform that happened in Indonesia since the ending a period of new order governance in the 1998. To be able to hold out, education institute have to be drawn up to face the global life which is full of challenge, high competition and innovative. Management set of education based on local excellence or local potency require to get the serious attention in order to pushing development acceleration in the region. Elementary change in educational organization is the system of management centralistic turning into system of management decentralistic. This change claims the organization to conduct various adjustment in organizational component and also leadership style posed at by leader. By many changes, there come requisites of some schools managerial competencies.School management of this leadership dimension is the happening of motivating activities to staff in order to motivated them to work and yield the masterpiece which is good for and certifiable. In global era, claimed an ability and competencies which must be non-stoped developed along with innovations found in the field of education. Therefore headmaster is even also claimed to be earning its duty as agent of change which always cope to the happening of diffusion innovate at staff.